2006
DOI: 10.1111/j.1813-6982.2006.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

The South African Phillips Curve: How Applicable Is the Gordon Model?

Abstract: Is there a Phillips curve relationship present in South Africa and if so, what form does it take? Traditionally the method to establish whether or not there is a relationship between the output gap and the change in inflation is merely to regress the latter on the former. This yields the well-known augmented Phillips curve. However, Gordon has argued that this specification of the Phillips curve produces biased results. Instead, he puts forward and estimates successfully for several industrialised countries hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 29 publications
4
34
1
Order By: Relevance
“…Examples of these include: Kaseeram, Nicola and Mainardi (2004), Burger and Marinkov (2006), Geldenhuys and Marinkov (2006), Woglom (2005), Knedlik (2006), 2 Examples include: Smit and Burrows (2002), Arora and Bhundia (2003), Du Toit and Moolman (2003), Akinboade (2005), and Du Toit, Van Eyden and Ground (2006) and Fedderke and Schaling (2005).…”
Section: Literaturementioning
confidence: 99%
“…Examples of these include: Kaseeram, Nicola and Mainardi (2004), Burger and Marinkov (2006), Geldenhuys and Marinkov (2006), Woglom (2005), Knedlik (2006), 2 Examples include: Smit and Burrows (2002), Arora and Bhundia (2003), Du Toit and Moolman (2003), Akinboade (2005), and Du Toit, Van Eyden and Ground (2006) and Fedderke and Schaling (2005).…”
Section: Literaturementioning
confidence: 99%
“…Based on the results of his study, Phillips concluded that by accepting some degree of inflation, central banks could maintain lower rates of unemployment ( Van der Merwe, 2004:11). Phillips' conclusion led to major disagreements among economists on the existence of a relationship between inflation and unemployment and, consequently, the actions that should be taken to address the trade-off between these economic indicators (Friedman, 1968;Burger and Marinkov, 2006;Fischer, 1996;Mankiw, 2001). …”
Section: Theoretical Discussionmentioning
confidence: 99%
“…The study found that the 'optimal smoothing constant was that value of λ that least distorts the frequency information of the time series' (in this case, λ = 524 for quarterly data used to evaluate a business cycle with a frequency of ~7 years). The HP filter has been used to explore South African business cycles and estimate long-run output levels (see Burger & Marinkov 2006;Fedderke & Schaling 2005;Kaseeram, Nichola & Mainardi 2004;Woglom 2003). Drehmann et al (2010) found that λ = 1600 and λ = 25 000 performed poorly on historical data while λ = 125 000 and λ = 400 000 performed well with quarterly data.…”
Section: Goodness Of Fit T T T T T T Penalty For Deviationsmentioning
confidence: 99%